A Dictionary of Chemistry, Vol. I - Macquer, Pierre Joseph (Peter Elmsley, 1777)
Volume 1 of 3 of the second English edition of Pierre Joseph Macquer's (1718-1784) first edition Dictionnaire de chymie (1766), translated by James Keir (1735-1820). Macquer's Dictionnaire was one of the most significant chemical dictionaries of the period, containing lengthy descriptions rather than brief definitions. The text was subsequently revised and translated numerous times. Though Macquer is primarily recognized for his Dictionnaire, he also was involved in industrial applications of chemistry such as the development of porcelain, and the use of Prussian blue (ferric ferrocyanide) for dyeing. The dictionary contains more than 500 alphabetical entries, beginning with Acid and ending with Zinc. The dictionary entries are preceded by a preliminary discourse, an advertisement, and a preface by the translator. The title page is preceded by a fold-out table of chemical characters. Translator, Keir, notes deficiencies of the original and first edition English translation in his preface. To address these deficits, Keir has added notes, articles, an appendix, and plates to this second edition translation. The plates are intended to more fully describe chemical instrumentation. The appendix, A Treatise on the various kinds of permanently elastic Fluids, or Gases by Keir, describes discoveries concerning elastic fluids (of which Macquer was unfamiliar at the time of his original publication). The plates and appendix are found following the dictionary entries of the third volume.
Keywords: Gases; Chemistry--Dictionaries; Science--Terminology; Chemistry--Study and teaching